An investigation of online threat awareness and behaviour patterns amongst secondary school learners - Irwin, Michael Padric (Rhodes University, Faculty of Science, Department of Computer Science, 2013)
The research area of this work is online threat awareness within an information security context. The research was carried out on secondary school learners at boarding schools in Grahamstown. The participating learners were in Grades 8 to 12. The goals of the research included determining the actual levels of awareness, the difference between these and self-perceived levels of the participants, the assessment of risk in terms of online behaviour, and the determination of any gender differences in the answers provided by the respondents. A review of relevant literature and similar studies was carried out, and data was collected from the participating schools via an online questionnaire. This data was analysed and discussed within the frameworks of awareness of threats, online privacy social media, sexting, cyberbullying and password habits. The concepts of information security and online privacy are present throughout these discussion chapters, providing the themes for linking the discussion points together. The results of this research show that the respondents have a high level of risk. This is due to the gaps identified in actual awareness and perception, as well as the exhibition of online behaviour patterns that are considered high risk. A strong need for the construction and adoption of threat awareness programmes by these and other schools is identified, as are areas of particular need for inclusion in such programmes. Some gender differences are present, but not to the extent that, there is as significant difference between male and female respondents in terms of overall awareness, knowledge and behaviour.
Keywords: Computer security -- South Africa -- Grahamstown; Risk perception -- South Africa -- Grahamstown; High school students -- South Africa -- Grahamstown; Communication -- Sex differences -- South Africa -- Grahamstown; Internet and teenagers -- South Africa -- Grahamstown; Internet and teenagers -- Risk assessment -- South Africa -- Grahamstown; Internet -- Safety measures -- South Africa -- Grahamstown; Online social networks -- Social aspects -- South Africa -- Grahamstown